The Development of Blended Learning at Information and Communication Technology Subjects - Billy Tantono; Eveline Siregar; Robinson Situmorang (International Journal of Education, Information Technology, and Others, 2020)
Information and Communication Technology is one of the subjects taught at SMA Don Bosco 2 Jakarta. In the learning process, various problems were found, the learning material consisting of cognitive and practical learning required more time while the time provided was limited. The current condition is also a new challenge where the Covid19 pandemic occurs so you are required to study at home. This research was conducted using the Dick and Carey Research & Development (R&D) method integrated with the PEDATI blended learning design model. The research was conducted from January to October 2020, at SMA Don Bosco 2 Jakarta. The results of the study generally show that the quality of the prototype based on the validation of the material, media and instructional design expertsreview is 94%, 80%, and 82%. Meanwhile, based on the results of the one to one trial, the small group and the large group the quality obtained was 96%. After being applied, it got an N-Gain Score of 0.78 and was classified in the high category.